Hajatan as a Musical Celebration in Urban Space - Elyane Machfuzoh; Ignatius Aditya; Endang Suryana Priyatna (Fakultas Komunikasi, Sastra, dan Bahasa, 2024)
This research discusses the sonic experience, sense, and cultural production resulting from music and sounds at wedding celebrations (hajatan) in Bekasi urban spaces. Perspectives on differences in sonic experience, sense and cultural production are examined as a result of the reconstruction of the sounds, music and venue of the hajatan The aim of this research is to examine the differences and reconstruction of senses and sounds presented in different places but with the same theme, especially hajatan. Data was taken by observing the hajatan in the yard area and the wedding hall. Critical theory from Edensor's explanation of sonic rhythms of place is used to analyze sense, sonic experiences, music and sounds at hajatan The results of the research show that sound, music and place can create different senses, sonic experiences and different cultural productions. In this way, music and sounds are not only an accompaniment to the event, but also a means of presenting different senses and sonic experiences.